Would Travel Experiences or Possessions Make People Happier?. (February 2023) - Yang, Wan; Zhang, Ye; Wang, Yao-Chin
To inform consumption choices bring people greater happiness, it is necessary to identify the types of consumption with greater happiness-generating potential. Using an experimental design, this research demonstrates that tourism experiences tend to cultivate happiness better than possessions, by empirically testing a potential underlying mechanism of such superiority—tourism's potential to cultivate eudaimonia (i.e., the more enduring form of happiness that accounts for the bigger picture beyond the self) without explicit eudaimonic motives. The mechanism can aid the identification of forms of consumption that maximize happiness. This research makes multi-faceted contributions to the tourism and consumption literature on eudaimonia and happiness promotion, including how its revealed potential in implicitly cultivating eudaimonia renders tourism a better consumption choice than material possessions for happiness maximization. Practically, the study suggests how tourism experiences can be designed and marketed to capitalize on the eudaimonic potential.